Effect of ruthenium addition on molybdenum catalysts for syngas production via catalytic partial oxidation of methane in a monolithic reactor - Figen, Halit Eren; Baykara, Sema Z. (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
Hydrogen is mainly produced from hydrocarbon resources. Natural gas, mostly composed of methane, is widely used for hydrogen production. As a valuable feedstock for 'Fischer Tropsch' (FT) process and 'Gas to Liquids' (GTL) technology, syngas production from catalytic partial oxidation of methane (CPOM) is gaining prominence especially owing to its more desirable H-2/CO ratio; relatively less energy consumption, and lower investment, compared to steam reforming processes (SMR), the leading technology. In the present study, effect of ruthenium (Ru) addition on molybdenum (Mo) catalysts for syngas production from methane (CH4) via partial oxidation in a monolithic reactor was investigated. Mo based catalysts supported on Nickel (Ni) and Cobalt (Co) metal oxides and Ni-Co bimetallic oxides and their Ru added versions were developed, characterized, and tested for performance in a monolithic type reactor system. Catalyst activity was investigated in terms of H-2 and CO selectivity, CH4 conversion; and CO2 emission and it is concluded that addition of Ru over the structure led to increase in catalytic activity and reduction in carbon deposition over the catalyst surface. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Syngas; Hydrogen; Methane; Partial oxidation; Molybdenum catalyst; Monolithic reactor; SYNTHESIS GAS-PRODUCTION; HYDROGEN-PRODUCTION; LA2O3 CATALYST; METAL; NI; NICKEL; COBALT; CONVERSION; CO; ZRO2; Chemistry; Electrochemistry; Energy & Fuels